Struggle for the spirit : religious transformation and popular culture in Brazil and Latin America - Lehmann, David (Cambridge [England] ; Cambridge, MA : Polity Press, 1996)
"Sophisticated study of religion and political culture compares rhetoric of 'the people' in the practices of Catholic Christian Base Communities and Pentecostal or Neo-Pentecostal congregations. Concludes that basista communities build small but powerful dissident elites among the poor, understandable in traditional terms of the relation between elite and popular culture, while crente congregations lead masses of the poor to break radically with what is rhetorically 'popular' and thus with familiar Brazilian political bargains"--Handbook of Latin American Studies, v. 58.
Includes bibliographical references (p. [229]-239) and index.
Keywords: Catholic Church -- Relations -- Pentecostal churches; Pentecostalism -- Brazil; Pentecostalism -- Latin America; Brazil -- Church history; Latin America -- Church history